The effect of thermoforming temperature and mould vent hole to the thermoplastic container made of 0.5 mm polypropylene (PP) sheet - Azree, Mohamad Azizi (2016)
Polypropylene is one of the thermoplastic that can be used undergo thermoforming process. Thermoforming process is a process that changes form of thermoplastic sheet from flat surface to dimensional shape. There are three types of thermoforming process. In this project, vacuum process had been chosen to change the shape of flat thermoplastic sheet. Thermoplastic can be formed any shape by undergo heating process using specific heat temperature and its can return to the solid shape upon cooling. Polypropylene (PP) had been choose to be main raw material to form plastic container. The properties of PP sheet are lower density, higher softening point depend on thickness and good resist to fatigue issue. Therefore, the main objective on this project is to prepare plastic container using own fabricated thermoforming machine. Preparation of the design container, design and fabricate mould is the main important process to form a good container. Temperature and number of vent holes are the parameter that had been set to know the different of each container. The result shows that temperature 155 °C is an ideal temperature for 0.5 mm PP sheet and 4 vent holes will get a good appearance result than 1 vent holes.